PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 012 TAMBAK KECAMATAN LANGGAM - Regina Misyah Aylia; Muhammad Fendrik; Erlisnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve mathematics learning outcomes of fifth grade students at SDN 012 Tambak Kecamatan Langgam through the implementation of the Project Based Learning (PjBL) model. This research used Classroom Action Research (CAR) consisting of two cycles, where each cycle included planning, implementation, observation, and reflection stages. The subjects of this study were 16 fifth grade students consisting of 7 male students and 9 female students. Data collection techniques used were observation, tests, project assessment, and documentation. The results showed that the implementation of the Project Based Learning model was able to improve student learning outcomes and learning activities. Student learning completeness increased from 56% before the action to 75% in cycle I and increased again to 87.5% in cycle II. The average N-Gain score in cycle I was 0.455 with moderate criteria, while in cycle II it increased to high criteria. Student learning activities also increased in every cycle because students were actively involved in project activities, group discussions, and problem solving related to real life. Thus, the implementation of the Project Based Learning model can improve mathematics learning outcomes of fifth grade students at SDN 012 Tambak Kecamatan Langgam.